Um método de avaliação de fatores de risco na implementação da produção enxuta - Silva, Tâmara Machado Fagundes da (2019)
The lean production implementation (LPI) is not a simple, quick and easy process. It requires a change in the mindset and know-how about the current activities and, due to this complexity, many companies have failed to implement the lean philosophy. Within this context, it is possible to verify the existence of several barriers, difficulties and risks that directly affect the result of lean implementation. Accordingly, this work aims to develop a risk factor assessment method for lean production implementation to prioritize and offer actions to mitigate risk factors that have the most significant impact on LPI failure. For this purpose, it was necessary to conduct first a literature review on lean risks, classifying them into types, subtypes and factors. Then, it proceeded with the adaptation of the failure mode and effect analysis (FMEA), replacing the traditional criteria by severity, probability of occurrence and ease of mitigation of risk factors in LPI. As a result, the proposed method provides a risk priority number (RPN) by multiplying the three criteria. From the prioritization process, it is possible to understand which risk factors should be addressed and mitigated through corrective and/or preventive actions. The method was tested by a case study in a chemical industry that had already implemented lean production. In the case study, 25 risk factors were identified and evaluated according to the severity. Following the case study, experts assessed the probability of occurrence and the ease of mitigation of the risk factors found in the case study. After calculating the RPN, 16 risk factors were prioritized and actions were proposed to assist the lean implementation leaders in risk management. From the empirical findings, it was concluded that the proposed method is suitable for its purpose, establishing a general assessment of risk factors in the implementation of lean production.